Effect of human blood groups on Leishmania dnovani growth in vitro (World Journal of Experimental Biosciences, 2016)
Visceral leishmaniasis (VL), a disease caused by Leishmania donovani, is still a health problem and a common parasitic infection. Several questions related to this disease have been raised that have still no answer in spite of new scientific developments in recent years. This study was performed to investigate the effect of human blood group types (O-, A+, A-, B+, B-, AB+ and AB-) on L. donovani growth rate in vietro. The growth rate of L. donovani was increased during fourth days in media supplemented with all types of blood groups. In fifth day, growth rate of L. donovani was significantly decreased in media supplemented with the blood group type (O-, A+, A-, B+, B-, AB+ and AB-) compare with L. donovani growth rate in media supplemented with blood group type (O+). The lowest growth rate of L. donovani was seen in media supplemented with the blood group type (AB+). Taking together, there is an association between L. donovani growth rate in vitro and the supplemented human blood group. These results indicate that it is possible to culture Leishmania parasite in axenic culture supplemented with human blood, especially the blood type O +.